Fundamentals of animal science - Scanes, Colin (Clifton Park, New York : Delmar Cengage Learning, 2011)
Suitable for college freshman, this title covers both companion and production animals and reviews key topics like reproduction, nutrition, genetics, and diseases at an introductory level